Saññā Khandha: One of the Priorities in Education and Life Development - ปุญฺญจาโร พระครูสมุห์เดือน; จิตตะมาก กรรมาธิการ (Journal of Educational Review Faculty of Education in MCU, 2018)
Saññā Khandha or perception is one of the five most important components of life and it is included in the Five Aggregates in Buddhism. The Five Aggregates consist of corporeality or the whole parts of the body, sensation or feeling from the contact, perception or memory, mental formation and consciousness. Perception or memory is useful for living, a life experience for the development and to prevent the repletion of mistakes. It is also beneficial to study as a knowledge store for a base of thought. The disadvantage of perception is to take part in self-harm, but there is a way to fix it and prevent it.